Mapping how responsibility for poor diets is framed in the United Kingdom: a scoping review - Serrano-Fuentes, Nestor; Ellett, Lyn; Vogel, Christina; Baird, Janis; Tavares, Nuno; Portillo, Mari Carmen (Public health nutrition, 2025)
To identify and present (i) how responsibility for poor diets in the UK is framed across the public, mass media and the government and (ii) how groups experiencing socio-economic disadvantage are presented within this framing. A scoping review of peer-reviewed literature was conducted using six databases. A systematic narrative synthesis guided by qualitative content analysis was applied to summarise the findings. Thirty-six articles were included. Studies exploring public perceptions of poor diets acknowledged personal and broader systems drivers, with individual responsibility predominating across studies. Research analysing media portrayals showed similar patterns of individual responsibility among right-leaning newspapers, which focused on individual lifestyle changes. However, left-wing newspapers highlighted the role of the food industry and the government. Studies analysing government policies identified citizens as the primary agents of change through rational decision-making. Framing from socio-economically disadvantaged groups showed a preference for prioritising their own choice, but were limited by household income, food prices and family food preferences. Policies and media portrayals provided limited emphasis on these populations, with individual responsibility narratives prevailing. The framing of responsibility for poor diets in the UK centred on the individual, obscuring the powerful influence of food manufacturers and retailers and the role of government in providing safe, healthy environments for all. This review highlights the urgent need to challenge this narrative, with the public health nutrition community working collectively to force a radical shift in public, media and policy framing and incite strong regulatory action by governments.